Calidad de vida laboral, autoestima y desempeño en el trabajo de los profesionales de la administración pública y privada en el Perú - Loli Pineda, Alejandro Erasmo (2020)
The objective of this research is to establish the relationship between quality of work life, self-esteem and job performance in a sample of 447 professionals of different specialties who work in public and private organizations in Perú and who were studying postgraduate studies (second specialty, master's and doctorate programs) in several universities, to whom three reliable and valid instruments were applied. The results showed a high level of quality of work life, self-esteem and high performance, decreasing this percentage to a moderate level and then to the low level. On the other hand, there is a significant and positive correlation between quality of work life, self-esteem and job performance, allowing to deduce that the higher the quality of working life, the level of self-esteem improves and as a consequence there is a job performance improvement. The analysis of the quality of working life, self-esteem and job performance to determine the differences when intervening the socio-demographic variables, allowed to find that there are only differences in the quality of working life when the remuneration intervenes, the place of origin, the job seniority and the years of service in the organization. While we find differences in self-esteem when only years of service in the organization intervene. When job performance is analyzed, none of the socio-demographic variables have an effect, the behavior is homogeneous.